ANALISIS FAKTOR PENYEBAB KETERLAMBATAN PROYEK PEMBANGUNAN GEDUNG LABORATORIUM TERPADU DAN PERPUSTAKAAN MAN 1 MALUKU TENGAH - Ervina Azhari; La Mohamat Saleh; Meyke Marantika (Jurusan Teknik Sipil, 2023)
Construction projects are a series of activities related to the process of developing infrastructure within a predetermined time frame by estimating the time required to complete the project. Delays in project planning can occur due to various factors. This also happened in the construction of the Integrated Laboratory and Library Building Project at MAN 1 Central Maluku, which experienced delays caused by several factors, including delays in the project due to factors such as labor, materials, design, situation, equipment, finance, site characteristics, and external factors. However, the factors that significantly and dominantly influence the delays are not yet known. Therefore, the purpose of this research is to identify the significant and dominant factors causing project delays. The analytical method used is regression analysis, which includes T-tests and F-tests. Based on the research results, the significant factors influencing project delays are the lack of availability of labor (labor factor), delay in the delivery of materials (material factor), equipment productivity (equipment factor), and financial difficulties of the contractor (financial factor). The most dominant factor influencing project delays is the labor factor, with a beta value of 1.198, indicating a lack of labor availability.